Low Bleeding Rates with Increase or Maintenance of Physical Activity in Patients Treated with Recombinant Factor IX Fc Fusion Protein (rFIXFc) in the B-LONG and Kids B-LONG Studies - Kulkarni, Roshni; Shapiro, Amy D; Windyga, Jerzy; Ragni, Margaret V; Pasi, K John; Ozelo, Margareth Castro; Tsao, Elisa; Mei, Baisong (Blood, 2015)
Background: The phase 3 B-LONG and Kids B-LONG studies demonstrated low annualized bleeding rates (ABRs) with rFIXFc prophylaxis in subjects with severe hemophilia B. Compared with prestudy FIX treatment, rFIXFc prophylaxis reduced weekly factor consumption and infusion frequency. Aims: To evaluate the effect of rFIXFc on subjects' physical activity across age groups using a subject-reported assessment and to examine ABRs with respect to change in physical activity and prestudy treatment regimen (prophylaxis or episodic) in B-LONG and Kids B-LONG. Methods: Previously treated males with severe haemophilia B (≤ 2 IU/dL endogenous FIX activity) were eligible for B-LONG (≥ 12 years of age) and Kids B-LONG (<12 years of age). Subjects in B-LONG were enrolled into 1 of 4 treatment arms: Arm 1, weekly prophylaxis; Arm 2, individualized interval prophylaxis; Arm 3, episodic treatment; or Arm 4, perioperative management (not included in this analysis). All subjects in Kids B-LONG started on weekly rFIXFc prophylaxis. There were no restrictions on physical activity in either study. Physical activity assessments were conducted at Weeks 4, 16, 26, 39, and 52 (B-LONG) and Weeks 3, 12, 24, 36, and 50 (Kids B-LONG). At each visit after their first rFIXFc dose, subjects were asked to report activity levels relative to their prior study visit as: more (or more intensive), fewer (or less intensive), or about the same amount of physical activities. To summarize each subject's change in physical activity during the study compared with baseline, subjects were classified into one of 4 groups: more, the same, less, or undetermined. Within each treatment group, prestudy and on-study ABRs were analyzed according to change in physical activity category and prestudy regimen. Analyses included all subjects who received ≥ 1 dose of rFIXFc during the efficacy period and who completed ≥ 1 physical activity assessment. Results: This analysis included 112 subjects from B-LONG and 30 subjects from Kids B-LONG. The majority of subjects in both studies reported more or the same amount of physical activity during the study; few subjects reported less physical activity. Percent of subjects with changes in physical activity levels (more, same, less, undetermined) in B-LONG were: Arm 1 (n = 60), 35%, 42%, 7%, 17%; Arm 2 (n = 25), 48%, 28%, 16%, 8%; Arm 3 (n = 27), 30%, 26%, 15%, 30%; and in Kids B-LONG (n = 30) were: 57%, 20%, 10%, 13%, respectively. Similar physical activity results were observed in subjects with and without target joints at baseline. Median on-study ABRs with rFIXFc prophylaxis were low in B-LONG and Kids B-LONG for all categories of change in physical activity; for subjects on prestudy prophylaxis who reported more or similar physical activity during B-LONG/Kids B-LONG, median ABRs with rFIXFc were similar or lower compared with prestudy ABR (Table). Summary/Conclusion: The majority of subjects in B-LONG (71%) and Kids B-LONG (77%) maintained or increased physical activity levels during the study. ABRs were low in both studies, regardless of change in physical activity. These results suggest that people with severe hemophilia B across age groups may maintain or increase their physical activity levels with rFIXFc while also maintaining low bleeding rates with reduced infusion frequency. Table 1Prestudy and On-study Median (IQR) ABR by Physical Activity Level in B-LONG and Kids B-LONGParent study:B-LONGKids B-LONGOn-study rFIXFc prophylaxis:Arm 1 (weekly)Arm 2 (individualized interval)WeeklyPrestudy FIX regimen:Prophylaxis(n = 30)Episodic(n = 28)Prophylaxis(n = 13)Episodic(n = 13)Prophylaxis(n = 30)Median (IQR) ABR by physical activity categoryMoren = 6n = 11n = 5n = 5n = 17Prestudy6.00 (1.00, 15.00)14.00(11.00, 28.00)1.00(0, 1.00)25.00(22.00, 25.00)2.00(0, 3.00)On-study4.76 (3.09, 5.62)3.13(1.14, 4.34)0(0, 0.72)2.19(1.66, 2.61)2.09(0, 3.13)Samen = 15n = 10n = 2n = 5n = 6Prestudy1.00(1.00, 6.00)26.00(20.00, 40.00)4.00(1.00, 7.00)33.00(27.00, 39.00)2.50(0, 3.00)On-study1.13(0, 2.30)2.62(0.99, 5.23)1.15(0, 2.30)1.09(0, 4.43)0.53(0, 2.90)Lessn = 3n = 0n = 2n = 1n = 3Prestudy0(0,0)--3.00(2.00, 4.00)22.005.00(2.00, 6.00)On-study0(0,0)--3.78(0, 7.56)01.85(1.06, 5.43)Undeterminedn = 4n = 5n = 1n = 1n = 4Prestudy4.50(2.50, 8.00)25.00(20.00, 40.00)4.0012.007.00(3.50, 13.00)On-study3.76(1.76, 5.35)1.04(0, 1.16)03.122.21(1.09, 3.92)ABR, annualized bleeding rate; IQR, interquartile range. Kulkarni:Baxter: Membership on an entity's Board of Directors or advisory committees, Research Funding; Bayer: Membership on an entity's Board of Directors or advisory committees, Research Funding; Novo Nordisk: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Pfizer: Membership on an entity's Board of Directors or advisory committees; Kedrion: Membership on an entity's Board of Directors or advisory committees; BPL: Membership on an entity's Board of Directors or advisory committees; Biogen: Research Funding, Speakers Bureau. Shapiro:Baxalta, Novo Nordisk, Biogen, ProMetic Life Sciences, and Kedrion Biopharma: Consultancy; Biogen: Speakers Bureau; Bayer Healthcare, Baxalta, Biogen, CSL Behring, Daiichi Sankyo, Kedrion Biopharma, Octapharma, OPKO, ProMetic Life Sciences, PTC Therapeutics, and Selexys: Research Funding; Baxalta, Novo Nordisk, Biogen,: Membership on an entity's Board of Directors or advisory committees. Windyga:Baxalta, Novo Nordisk, and Biogen: Research Funding; Baxalta, Novo Nordisk, Sanofi, CSL Behring, Bayer, and Pfizer: Honoraria; Baxalta, Novo Nordisk, Sanofi, Biogen, CSL Behring, Bayer, and Pfizer: Membership on an entity's Board of Directors or advisory committees. Ragni:SPARK: Research Funding; Alnylam: Research Funding; Bristol Myers Squibb: Research Funding; Biomarin: Research Funding; Shire: Membership on an entity's Board of Directors or advisory committees, Research Funding; Bayer: Research Funding; Genentech Roche: Research Funding; Pfizer: Research Funding; CSL Behring: Research Funding; Vascular Medicine Institute: Research Funding; Dimension: Research Funding; Baxalta: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; Biogen: Research Funding; Tacere Benitec: Membership on an entity's Board of Directors or advisory committees. Pasi:Octapharma: Research Funding; Biogen, Octapharma, Genzyme, and Pfizer: Consultancy, Honoraria. Ozelo:Baxter: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Biogen: Research Funding; Novo Nordisk: Research Funding, Speakers Bureau. Tsao:Biogen: Employment, Equity Ownership. Mei:Biogen: Employment, Equity Ownership.